Copolymerization of butyl vinyl ether and methyl methacrylate by combination of radical and radical promoted cationic mechanisms - Braun, Harald; Yagci, Yusuf; Nuyken, Oskar (Elsevier BV, 2002)
Butyl vinyl ether (BVE) and methyl methacrylate (MMA) mixtures were polymerized by using free radical initiators in conjunction with a cationic initiator such as diphenyl iodonium salt. Polymerization mechanism involves free radical polymerization of MMA which is switched to cationic polymerization of BVE by addition of growing poly(MMA) radicals to BVE and subsequent oxidation of electron donating polymeric radicals to the corresponding cations by iodonium ions. Two representative bifunctional monomers, ethylene glycol divinyl ether (EGDVE) and ethylene glycol dimethacrylate (EGDMA) were also used together with MMA and BVE, respectively, in photo and thermal crosslinking polymerizations. Vinyl ether and methacrylate type monomers can successfully be copolymerized by this double-mode polymerization under photochemical conditions.